Archetypical barriers to adapting water governance in river basins to climate change. Issue 3 (30th October 2017) - OBERLACK, CHRISTOPH; EISENACK, KLAUS
Abstract: Can we explain barriers to adaptation of collective action to changes in the natural environment? One reason for adaptation is the impacts of climate change. Ample case study evidence shows that such adaptation is rarely a smooth process. However, generalisable patterns of how and why barriers arise remain scarce. The study adopts a collective action perspective and the archetypes approach in a meta-analysis of 26 selected publications to explain how barriers arise in specific conditions. Focusing on adaptation of water governance in river basins, the study finds 21 reappearing patterns. Less well-established patterns relate to water property rights, hydrological standards, adaptation externalities, non-climatological uncertainty and vertical coordination. Results further show how barriers impede collective action in specific ways. The paper precisely introduces the archetypes approach, and shows that reported problems in adapting collective action under climate change arise from attributes of actors and pre-existing institutions rather than biophysical characteristics.